AGRARIAN CHARACTER UKRAINIAN REVOLUTION 1917 - 1921 - Lazurenko, Valentyn (Ukrainian Peasant, 2021)
Review of the monograph “Kornovenko, S. & Zemzyulina, N. & Kovaleva, N. & Malinovsky, B. & Masnenko, V. & Morozov, A. & Mikhailyuk, O. & Pasichna, Yu. Peasants, land and power during the Ukrainian Revolution (1917 - 1921). Cherkasy, 2020”